2018
DOI: 10.3389/fphys.2018.00686
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-155 Regulates the Th17/Treg Ratio by Targeting SOCS1 in Severe Acute Pancreatitis

Abstract: Acute pancreatitis (AP) is a serious condition associated with intestinal barrier disruption or inflammation of the pancreatic tissue. Specific microRNAs are involved in the pathogenesis of AP, during which IL-17-producing CD4+ T helper (Th17) cells accumulate in the pancreas. In this study, significantly increased levels of miR-155 were detected in clinical samples from patients with AP, and overexpression of miR-155 correlated with severe AP (SAP). To identify the effect of miR-155 on T cell differentiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 44 publications
2
68
1
Order By: Relevance
“…It is also a tumor suppressor and therefore inactivated during malignant transformation, and tumor initiation and metastasis [47,48]. Several targets of miRNA-155 have been identified in recent years, such as the BRG1 [49] and FOXO3a [50] in lymphoma, and SOCS1 in severe acute pancreatitis [51]. Parnas et al predicted 9 common target genes of MDV1-miR-M4, KSHV-miR-K11 and HAS-miR-155, and 4 of MDV1-miR-M4 and HAS-miR-155 in human B cells and chicken T cells, which includes RORA [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is also a tumor suppressor and therefore inactivated during malignant transformation, and tumor initiation and metastasis [47,48]. Several targets of miRNA-155 have been identified in recent years, such as the BRG1 [49] and FOXO3a [50] in lymphoma, and SOCS1 in severe acute pancreatitis [51]. Parnas et al predicted 9 common target genes of MDV1-miR-M4, KSHV-miR-K11 and HAS-miR-155, and 4 of MDV1-miR-M4 and HAS-miR-155 in human B cells and chicken T cells, which includes RORA [32].…”
Section: Discussionmentioning
confidence: 99%
“…regulators of effector CD8(+) T cells as they affect cytokine signaling through STAT5 (Dudda et al, 2013). Wang et al found that in acute pancreatitis, miR-155 targets SOCS1 to regulate the Th17 cell/Treg ratio, thus mediating disease severity (Wang et al, 2018). MiR-155 was also shown to function as a proproliferative regulator during liver regeneration by facilitating the cell cycle and directly targeting SOCS1 (Lin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also a tumor suppressor and therefore inactivated during malignant transformation, and tumor initiation and metastasis [47,48] . Several targets of miRNA-155 have been identified in recent years, such as the BRG1 [49] and FOXO3a [50] in lymphoma, and SOCS1 in severe acute pancreatitis [51] . Parnas et al predicted 9 common target genes of MDV1-miR-M4, KSHV-miR-K11 and HAS-miR-155, and 4 of MDV1-miR-M4 and HAS-miR-155 in human B cells and chicken T cells, which includes RORA [32] .…”
Section: Discussionmentioning
confidence: 99%